The Hippo–YAP/TAZ Signaling Pathway in Intestinal Self-Renewal and Regeneration After Injury - Deng, Feihong; Wu, Zengrong; Zou, Fei; Wang, Su; Wang, Xuehong (Frontiers in Cell and Developmental Biology, 2022)
The Hippo pathway and its downstream effectors, the transcriptional coactivators Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ), control stem cell fate, cell proliferation and differentiation and are essential for tissue self-renewal and regeneration. YAP/TAZ are the core components of the Hippo pathway and coregulate transcription when localised in the nucleus. The intestinal epithelium undergoes well-regulated self-renewal and regeneration programmes to maintain the structural and functional integrity of the epithelial barrier, which prevents luminal pathogen attack and facilitates daily nutrient absorption and immune balance. Inflammatory bowel disease (IBD) is characterised by chronic relapsing inflammation of the entire digestive tract, and impaired mucosal healing is a prominent biological feature of IBD. Intestinal self-renewal is primarily dependent on functional intestinal stem cells (ISCs), especially Lgr5+ crypt base columnar (CBC) cells and transient-amplifying (TA) cells in the crypt base. However, intestinal wound healing is a complicated process often associated with epithelial cells and mesenchymal and immune cells in the mucosal microenvironment. Upon intestinal injury, nonproliferative cells rapidly migrate towards the wound bed to reseal the damaged epithelium, followed by cell proliferation and differentiation. YAP is generally localised in the nucleus of Lgr5+ CBC cells, where it transcriptionally regulates the expression of the ISC marker Lgr5 and plays an important role in intestinal self-renewal. YAP/TAZ are the primary mechanical sensors of the cellular microenvironment, and their functions include expanding progenitor and stem cell populations, reprogramming differentiated cells into a primitive state and mediating the regenerative function of reserve stem cells; thus, YAP/TAZ play extremely crucial roles in epithelial repair after damage. The present review provides an overview of the Hippo–YAP/TAZ signalling pathway and the processes of intestinal self-renewal and regeneration. Notably, we summarise the roles of YAP/TAZ in the phases of intestinal self-renewal and regeneration to suggest a potential strategy for IBD treatment.